Assessing the Impact of Blockchain Technology on Financial Reporting and Audit Practices (Asian Business Research, 2024)
The significant influence of blockchain technology on contemporary financial reporting and auditing procedures is examined in this paper. The rapid spread of blockchain technology brought about a new era in financial data management, which can completely transform the accounting ecosystem's efficiency, security, and transparency. This study explores the various ramifications of blockchain adoption in accounting, concentrating on how it affects regulatory compliance, audit trail integrity, cost-effectiveness, smart contracts, and financial reporting accuracy. This study aims to clarify blockchain technology's advantages and challenges to accounting professionals, regulators, and auditors by analyzing its disruptive potential. With the help of growing regulatory frameworks and real-world use examples, it offers a thorough grasp of how financial reporting and auditing processes are changing in the blockchain era. The study also emphasizes the significance of understanding how blockchain technology changes traditional accounting practices as more companies incorporate it into their financial operations. It draws attention to the benefits of blockchain technology. Also, it emphasizes the need for flexibility and compliance with legal requirements to fully realize its potential in the fields of audit assurance and financial reporting. This investigation allowed us to provide accounting managers, professionals, policymakers, and other stakeholders with priceless knowledge of the potential for blockchain technology to revolutionize the accounting industry.